Inactivation of critically ranked carbapenem resistant bacteria and genes in a batch atmospheric plasma reactor - Iwarere, Samuel Ayodele (University of Pretoria, 2024)
Dissertation (MEng(Environmental Engineering))--University of Pretoria, 2023.